2007
DOI: 10.2527/jas.2006-620
|View full text |Cite
|
Sign up to set email alerts
|

Energy and nutrient digestibility in NutriDense corn and other cereal grains fed to growing pigs1,2,3

Abstract: Two experiments were conducted to measure the energy and nutrient digestibilities in NutriDense corn and other cereal grains. An additional objective was to evaluate the effect of balancing diets with AA on the values measured for DE and ME of corn varieties. In Exp. 1, 6 growing pigs were fitted with a T-cannula in the distal ileum and allotted to a 6 x 6 Latin square design to measure apparent ileal digestibility (AID) and standardized ileal digestibility (SID) values for CP and AA in NutriDense corn, yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
49
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 17 publications
19
49
1
2
Order By: Relevance
“…In general, the AID of AA in RH barley were within the range of values reported in the literature (Fan and Sauer 1995;Nyachoti et al 1997;Reverter et al 1999). The SID values for AA obtained in the present study were similar to the values reported by Pedersen et al (2007) for regular barley. Although the barley samples did not have differences in SID of AA, because of the high absolute contents (Table 1) of AA in LP barley, the calculated SID contents for most of AA were higher (P B0.05) for LP barley (Table 2).…”
Section: Resultssupporting
confidence: 80%
“…In general, the AID of AA in RH barley were within the range of values reported in the literature (Fan and Sauer 1995;Nyachoti et al 1997;Reverter et al 1999). The SID values for AA obtained in the present study were similar to the values reported by Pedersen et al (2007) for regular barley. Although the barley samples did not have differences in SID of AA, because of the high absolute contents (Table 1) of AA in LP barley, the calculated SID contents for most of AA were higher (P B0.05) for LP barley (Table 2).…”
Section: Resultssupporting
confidence: 80%
“…In wheat, lowest SID values are generally observed for lysine (Pedersen et al, 2007;Hennig et al, 2008), but also for threonine (Widyaratne and Zijlstra, 2007b). The low SID of lysine has been attributed to its relatively low content compared to the other AA in wheat (Fan et al, 1993).…”
Section: Crude Protein and Amino Acid Digestibilitymentioning
confidence: 89%
“…The database A database containing AID of CP and AA in 38 barley samples for pigs was extracted from a total of 26 peer-reviewed papers with data on AID of CP and AA in barley including studies of Baidoo and Liu (1998) (3);De Lange et al (1990) (1); Fan et al (1993) (1); Fan and Sauer (1995) (1); Fan and Sauer (2002) (6); Fernández-Fígares et al (2008) (1) ;Fuller et al (1994) (1); Furuya and Kaji (1991) (1); Green et al (1987) (1); Ige et al (2010) (2); Jørgensen et al (1997) (2); Lin et al (1987) (1); Nitrayová et al (2006) (1); Nyachoti et al (1997) (1); Pedersen et al (2007) (1); Perttilä et al (2002) (1); Reverter and Lindberg (1998) (1); Rowan and Lawrence (1986) (1); Sauer et al (1977) (1); Sauer et al (1981) (4); Schröder et al (1989) (1); Stein et al (1999) (1); Taverner et al (1981b) (1); Yin et al (1993) (1); Yin et al (2001a) (1) and Yin et al (2002) (1) (number of barley samples per study is given in brackets). The selection of these peer-reviewed papers was based on several criteria including (1) complete information on diet composition; (2) complete information on CP and AA contents of the diet and (or) barley; (3) use of barley as the only source of protein in the diet; (4) diets being devoid of feed additives.…”
Section: Methodsmentioning
confidence: 99%